The Contribution Of Waqaf Properties Toward Acehnese Dayah’s Educational Empowerment - Ruslan Razali (At-Tafkir, 2015)
Waqaf, throughout the Islamic history, serves tremendous dedications to sustain the Islamic development. For almost one and half millennium, waqaf is one of the key success factors in supporting the Islamic education. In the context of Aceh, waqaf has widely been used to fund the traditional institutions of education (Dayah). This study intent to examine the roles of waqaf properties in supporting the educational development, how dominant is the waqaf system has been perceived as an important function in Acehnese Dayah, and whether the spirit of generosity among Acehnese towards the Islamic education is reflected through the waqaf tradition. This research based on the interview sessions with the principal leaders of Dayahs in three different regions where the largest number of Dayah is found. The results of the study showed that Waqaf has played the significant roles in supporting the Islamic traditional education or dayah in Aceh, and become the important source for many dayah since waqaf properties are utilized for the purpose of facilitating, enhancing and achieving the educational processes towards the student development. Besides, waqaf system has been also perceived its important function in funding the dayah institutions via four ways; providing the infrastructure facilities of the Dayah, supporting the principal, teachers and other dayah educational staffs in conducting the teaching learning processes, managing the programs and activities, controlling and evaluation the rules and strategies towards better student’s achievement, preparing the financial assistance to the teachers and tutors, and by handling the daily operational cost of these institutions. The findings also mentioned that the Acehnese generosity towards the Islamic education has been reflected by community as their dedications through the waqaf donations. As the territory that the Islamic Sharia is implemented, waqaf should be reactualize in maximaling its contribution towards better educational development in Aceh.